IDENTIFICATION OF SCIENTIFIC ATTITUDE ON SENIOR HIGH SCHOOL STUDENTS IN SOLUBILITY AND SOLUBILITY PRODUCT CONCEPT - Ernita Vika Aulia; Findiyani Ernawati Asih (JPPIPA (Jurnal Penelitian Pendidikan IPA), 2020)
The main objectives of this study is to describe students' scientific attitudes on the solubility and solubility product concept before and after guided inquiry-based learning. The scientific attitude in this study includes four indicators, that is student attitudes towards science, the importance of science in life, student responses to science as a career, and student responses to learning science in school. Scientific attitudes play an important role in student decision making to develop scientific knowledge further, pursue careers in science, and use scientific concepts and methods in their lives. This study used a survey method for 40 students enrolled in the 2017/2018 academic year. Data obtained through questionnaires and observations of scientific attitudes during learning activities. The questionnaire technique consisted of a self-assessment sheet and an assessment sheet between friends, each containing 30 statements (positive and negative). This sheet was given before and after learning activities. Data were analyzed quantitatively and qualitatively according to the description. The results of scientific attitudes obtained from the self-assessment sheet and among friends are presented in Table 1. From the results of the study, it was shown that student attitudes towards science were the highest scores for the scientific aspects and there were differences in students' scientific attitudes before and after guided inquiry-based learning on the solubility and solubility product concept.Keywords: Scientific attitude, guided inquiry, solubility and solubility product concept